2015
DOI: 10.1111/1750-3841.13077
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Folin‐Ciocalteu and Prussian Blue Assays to Estimate The Total Phenolic Content of Juices and Teas Using 96‐Well Microplates

Abstract: Prussian Blue assay (PB) has been used as an alternative to Folin-Ciocalteu assay (FC) to estimate the total content of phenolic compounds in herbs and some natural products. In our study we showed that the advantages of PB assay over FC are its simplicity, low time consumption (15 min reaction as compared to 60 min reaction for the FC assay), lower usage of reagents (solutions are prepared in a mM base) and higher selectivity as compared to FC assay. Additionally, PB assay was proven to be reproducible and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(81 citation statements)
references
References 54 publications
4
71
0
6
Order By: Relevance
“…Nearly 100% recovery for F-C and DMAC (Table 2) indicates measurements very close to reference values. Similar recovery for F-C, 90% (Blainski, Lopes, & de Mello, 2013) and 98.20% (Margraf et al, 2015) have been reported. L-P recovery was much higher, 143.5 ± 0.32%, a value beyond the accepted range of 80% to 120% (U.S. Food and Drug Administration, 2015).…”
Section: Food Chemistrysupporting
confidence: 86%
See 1 more Smart Citation
“…Nearly 100% recovery for F-C and DMAC (Table 2) indicates measurements very close to reference values. Similar recovery for F-C, 90% (Blainski, Lopes, & de Mello, 2013) and 98.20% (Margraf et al, 2015) have been reported. L-P recovery was much higher, 143.5 ± 0.32%, a value beyond the accepted range of 80% to 120% (U.S. Food and Drug Administration, 2015).…”
Section: Food Chemistrysupporting
confidence: 86%
“…For F‐C, LOD and LOQ were 14.2 and 42.9 mg/L GA, respectively. Others have reported lower LOD and LOQ of 0.25 and 0.82 mg/L GA, respectively (Margraf, Karnopp, Rosso, & Granato, ). This difference could be attributable to stronger color intensity imparted by more concentrated F‐C reagent, resulting in greater slope of the analytical curve, and lower LOD and LOQ.…”
Section: Resultsmentioning
confidence: 94%
“…The total polyphenol content can be analyzed by relatively simple methods such as the Folin–Ciocalteau assay, or by considering peak areas identified by HPLC‐DAD . In the present study, we combined qualitative analysis of MS with total peak areas obtained by DAD.…”
Section: Resultsmentioning
confidence: 99%
“…The total phenolic content in the cookie extracts was estimated using the Prussian-Blue assay (Margraf et al, 2015). The results were expressed as mg gallic acid equivalents/100 g of cookie.…”
Section: Determination Of Total Phenolic Content and Antioxidant Actimentioning
confidence: 99%